Targeted sampling reduces the uncertainty in force of infection estimates from serological surveillance - Kim, Kiyeon; Ito, Kimihito (Frontiers in Veterinary Science, 2022)
Age bins are commonly used in serological studies of infectious diseases in wildlife to deal with uncertainty on ages of sampled animals. In this study, we analyze how age binning and targeted sampling in serological surveillance affect the width of 95% confidence interval (CI) of estimated force of infection (FOI) of infectious diseases. Using computer simulations and mathematical models, we show that the optimal target population that has the narrowest 95% CI differs depending on the expected FOI. Our results show that by tailoring targeted, age-based sampling to specific epidemiological situations we can substantially reduce the number of animals required to make inference on transmission risk.